Anglo-Soviet Relations, 1917-1921, Volume 2 : Britain and the Russian Civil War - Ullman, Richard H. (Richard Henry) (Book collections on Project MUSE., 2019)
At the end of World War I the British government found itself deeply mired in a Russian civil war aimed at destroying the infant Bolshevik regime. A year later this effort was in shambles despite massive assistance from abroad. Anti-Bolshevik forces were in retreat and soon were completely annihilated. During 1919 the British government concluded that the costs of bringing down Bolshevism in Russia were prohibitively high. This book is an account of how this conclusion was reached, and of the conflict over Russian policy between David Lloyd George and Winston Churchill. Richard H. Ullman is Associate Professor of Politics and International Affairs, Princeton University. Published for the Center of International Studies, Princeton University. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.